Novo ensino médio e a (des)integração entre educação-trabalho: uma análise documental dos projetos pedagógicos dos cursos técnicos integrados do IFTM - Campus Ituiutaba no contexto do neoliberalismo e das pedagogias das competências (2013 – 2022) - Pereira, Agnaldo Damasceno (2022)
We defend, as a central point, the thesis that in a capitalist society, orchestrated by the bourgeois State, the education offered to the working class will be dual and unilateral, different from what the dominant and middle layers of society will have access to. Thus, the approval of the “new” High School (Law 13,415/2017), despite the clashes and disputes that have been and are being fought, represents another capital tactic to guarantee the accumulation and co-optation of the working class, so that policies public education, the hegemonic pedagogy, especially of “competence”, and the curriculum itself (BNCC) are constitutive parts of the center of capitalism, but also with the consent and dependence of the national bourgeoisies, to preserve the economic, political and cultural power over the other economies, in particular the peripheral countries. In this way, the maintenance of a technical-professional education, present even in the IFs, aimed at the children of the working classes (manuals) is incapable of articulating and integrating broader general knowledge (propaedeutic), which hinders, even more, the transformations and the very condition to which we are immersed, as a commodity supplier country, capital strategy to “feed back its socio-metabolic system”. With this work, we conclude that Marxism continues to be a methodological framework and a fundamental critical reading to build forms of sociability that is not the imprisonment of subjectivity and human potential, despite those who insist on denying it, erasing it, forgetting it. it.